Development of Embedded Application for Receiver Processor Unit (International Journal of Engineering and Computer Science, 2017)
Electronic Warfare (EW) systems are used to meet the tactical and strategic requirements of the users for use on different platforms like ships, aircrafts, helicopters, ground vehicles and submarines. The ES system will have broad band and narrow band operations to meet the tactical and strategic needs of EW systems. Broad band operation is achieved by employing a Wide Open Receiver, which will achieve 100% Probability of Intercept(POI), whereas narrow band receiver will help in achieving higher sensitivity and better Range Advantage Factor(RAF) against Low Probability of Intercept(LPI) radars. Receiver Processor Unit (RPU) generates the controls for the Digitally Tuned Oscillator(DTO) and the switches in the BuiltIn Test Equipment (BITE) distribution network based on the BITE Command received from System Controller Display (SCD). The output of the RF Source is fed to the programmable attenuator to adjust the power levels required to check the dynamic range of the receiver. In this paper, the authors report development of an embedded application for RPU to generate the controls for various devices like switch filter bank, homodyne receiver etc. The embedded application is thoroughly tested for its functionality using given lookup table and the results are found to be satisfactory.